IDENTIFICATION OF Ralstonia solanacearum ISOLATED FROM A NEW HOST: Cosmos caudatus IN INDONESIA - Hanudin Hanudin; Kurniawan Budiarto; Budi Marwoto (SEAMEO BIOTROP, 2014)
The evolutionary dynamic of pathogenic microorganism might change pathogen-host interaction including the establishment of pathogen colonization in a new host. The information of the new host of devastating pathogens will serve a basis for their control method. An unknown bacterial wilt disease attacking wild cosmos (Cosmos caudatus) crop in Pacet-Cianjur, Indonesia was suspiciously caused a novel strain of Ralstonia solanacearum. The research was carried out to investigate the causal agent, characteristics and its grouping based on the morphological, physiological and biochemical properties and the relationship of the pathogen with the hosts. The results showed the incidence of bacterial wilt on wild cosmos was epidemiologically caused by the species complex of pathogen R. solanacearum. Based on the symptoms, morphological, physiological, biochemical and pathogenicity evaluations, the strain classified into group 7, race 1 and biovar 3 and group 7. This was the first report of the incidence of R. solanacearum hosted naturally in wild cosmos in Indonesia.